Accelerated Aging Test to Assess Vigor of Juglans Nigra Seeds. Issue 2 (2nd April 2020) - Flores, Patricia; Poggi, Damián; Gariglio, Norberto; Catraro, Marcela
ABSTRACT: The objective of this work was to develop a methodology for standardizing the Accelerated Aging test (AA) for J. nigra seeds. After different aging treatments, seeds were subjected to the standard germination test the results of which were expressed as the percentage of normal seedlings. Germination velocity index and mean time of maximum germination were also determined. Our results showed that storage at high temperature and relative humidity deteriorates black walnut seeds to the extent that their germination capacity is lost in only seven days. Bigger seeds had a higher percentage of normal seedlings and vigor, both under favorable storage conditions and when subjected to accelerated aging treatments. This work has clearly shown that vigor of J. nigra seeds should be assessed using AA periods no longer than 72 h. The most frequent abnormality observed in AA testing was seedlings with stubby roots and no secondary roots.